Use of Pomegranate peel powder as a low cost Adsorbent for the Decolorization of Azure C dye - Jassim Manshad, Maha; H. AL-ogaili, Alaa; Al-Ghanimi, Hussein Hazim; H.Chafat, Ali (Pure Sciences International Journal of Kerbala, 2024)
In the current research, the modified pomegranate surface was used.It showed good results and high efficiency in removing pollutants from aqueous solutions. It was used to remove the azure C dye from its aqueous solutions, which is considered one of the harmful dyes.The following conditions were studied(equilibrium time, weight, pH function, temperature), The removal rate was 99.17% at a time of 10min, a weight, a temperature of 250C, and an acid pH 8, Thermodynamic constants(ΔS, ΔH, ΔG) and adsorption isotherms(Langmuir, Freundlich) were also examined.